The Relationship Between Leadership and Integrity: A Systematic Review and Meta-Analysis - Roni Ekha Putera; Nika Saputra; Edi Hasymi; Aqil Teguh Fathani; Tengku Rika Valentina; Nabilaa Binti Mohamed; Tirza Haqia Purnama (Journal of Social and Policy Issues, 2026)
This study reviews how integrity is conceptualized and evidenced in leadership research and clarifies what is known about its outcomes and mechanisms. Guided by PRISMA 2020, we searched Scopus for English, peer‑reviewed journal articles (2011–2022). After duplicate removal, screening, and eligibility checks, 67 articles were appraised with an adapted quality checklist and synthesized via descriptive mapping and thematic analysis. The literature clusters into twelve streams, dominated by leader behavioral integrity and ethical leadership. Across sectors, integrity is most consistently associated with follower trust, work engagement, and performance, often through transparent communication and psychological safety. Yet conceptual ambiguity remains because integrity is alternately treated as word–deed alignment, virtue‑based wholeness, and follower attributions. We propose an integrative framework linking these views to influence theories and identify gaps: limited longitudinal and multilevel evidence, weak cross‑cultural measurement, and underdeveloped connections to governance and anti‑corruption outcomes. Practical implications are offered for integrity‑based leadership development and accountability systems. The review also highlights boundary conditions (sector and culture) and outlines a focused agenda for future meta‑analytic and policy-relevant research.